Intervening to reduce sedentary behavior among African American elders: the "Stand Up and Move More" intervention - Brianna N. Leitzelar; Neda E. Almassi; Susan J. Andreae; Rachelle Winkle-Wagner; Lisa Cadmus-Bertram; Luis Columna; Kevin M. Crombie; Kelli F. Koltyn (Tabriz University of Medical Sciences, 2024)
Background: Reducing sedentary behavior is a promising intervention target for improving health for older adults; however, few interventions include African American communities. The purpose of this research was to extend the reach of an effective sedentary behavior intervention to African American elders. Methods: Two pilot studies assessed the feasibility (retention, adherence, and safety) and acceptability (participant and leader perspectives) of a 4-wk "Stand Up and Move More" (SUMM) intervention. Sedentary behavior (self-reported and monitor-derived), function (short physical performance battery), and quality of life (SF-36) were measured at baseline (wk0), postintervention (wk4), and follow up (wk12; study 1) to examine preliminary effectiveness of the intervention. Participants (N=26) attended SUMM or an attention-matched stress management intervention (study 2). The magnitude of treatment effects were determined using Hedge's g effect size calculations [small (g=0.20 to 0.49), moderate (g=0.50 to 0.79), large (g>0.80)]. Results: Retention and adherence rates ranged from 50%-100% and 80%-100%, respectively. There were no adverse events. Participants expressed high satisfaction, and the leader of the SUMM intervention indicated that the intervention content was beneficial. Hedges' g revealed negligible to small changes in sedentary behavior (g<0.50) following SUMM. There were moderate to large improvements in function (g=0.51-0.82) and quality of life (g=0.54-1.07) from wk0 to wk4 in study 1; and moderate to large improvements in function (g=0.51-0.88) from wk0 to wk4 in study 2. There was a moderate improvement in quality of life (SF-36 emotional role limitations g=0.54) in the SUMM group only. Conclusion: Given its feasibility, safety, and acceptability, SUMM may be a promising intervention to improve functioning and well-being among African American elders.